Pengaruh Harga, Kualitas Produk, Citra Merek, Dan Kemasan Terhadap Keputusan Pembelian Beras BULOG SPHP Di Kota Surabaya - Lestari, Renita Dwi; Widayanti, Sri; Wijayati, Prasmita Dian (Fakultas Pertanian - UMJ, 2025)
Rice is a staple food for Indonesian society, making the factors influencing rice purchasing decisions crucial in marketing. This study aims to analyze the influence of price, product quality, brand image, and packaging on the purchasing decision of BULOG SPHP rice in Surabaya. The research employs a quantitative approach with a non-probability sampling method, specifically accidental sampling, involving 90 respondents. Data were collected through questionnaires and analyzed using the SEM-PLS technique with SmartPLS 4 software. The results indicate that price, product quality, and packaging have a positive and significant influence on purchasing decisions, whereas brand image does not have a significant impact. Stable and affordable pricing is the primary factor influencing consumer decisions, followed by good product quality and attractive, functional packaging. These findings suggest that marketing strategies focusing on price, quality, and packaging are more effective in increasing consumer interest in BULOG SPHP rice.